Comparison of the synthesis of s, p, d, and f block simple oxides of MgO, SnO2, NiO, and CeO2 nanostructured materials - S. Balamurugan; J. Jainshaa; S.A. Ashika (Results in Chemistry, 2023)
The s, p, d, and f block simple oxides of MgO, SnO2, NiO, and CeO2 materials were synthesized by precipitation method and compared in this article. The tetragonal SnO2 and cubic CeO2 phases form in a single-step synthesis process. On the other hand, upon annealing (500 °C/3h), the as-prepared trigonal (P-3 m1 (164)) Mg(OH)2 and Ni(OH)2 phase materials transform into cubic (Fm-3 m (225)) oxides of MgO and NiO. The difference in the ionic radii of these ions (Mg2+, Sn4+, Ni2+, and Ce4+) is significantly reflected in the variation in the refined lattice parameters. The nanostructured as-prepared materials (SnO2 and CeO2) obtained in a single-step process show the crystalline size (average) of 2 nm. Conversely, the samples of MgO and NiO phases obtained through annealing show 13.76 nm and 21.44 nm, respectively. The as-prepared materials show the weight loss of 33.3%, 31.7%, 15.4%, and 16.1% at the end temperature (1000 °C) for the Mg(OH)2, Ni(OH)2, SnO2, and CeO2 phases, respectively. The different FTIR bands are seen between the wavenumber 4000 and 400 cm−1 for the present series samples.